Septal Ulcer After Nasal Filling with Hyaluronic Acid - Souza Felix Bravo, Bruna (J Clin Aesthet Dermatol, 2021)
Nonsurgical rhinoplasty is a good treatment choice when surgery is not a viable option. However, serious complications, including blindness or cerebral ischemia, can occur given this area is one of external and internal carotid anastomosis. Here, we describe a case of a patient with a septum ulcer secondary to local ischemia postnasal fillling with hyaluronic acid without skin lesion. Due to the rarity of the condition, her diagnosis was made late, but she was treated with hyaluronidase and showed total resolution.